Analisis Pengolahan Limbah Sabut Kelapa pada PT. Coco Berdikari Desa Karya Maju Kecamatan Sungai Saren Kabupaten Tanjung Jabung Barat - Nurul Anggraini; Ovie Yanti; Erik Yusdian; Miduk Hosea Siahaan; Helma Yulita; Rani Kurniawati; Rut Yolanda (STIKes Ibnu Sina Ajibarang, 2024)
Coir is one of the components of coconut that can be produced and decomposed into derivative products that have economic value. PT Coco Berdikari, established in 2018 in Karya Maju Village, Sungai Saren Sub-district, Tanjung Jabung Barat Regency, is a pioneer in the coconut fibre processing industry in the region. The company's main focus is processing coconut fibre into cocopeat, cocosheet and cocofiber. Based on the results of the research, it was found that the challenges in coir waste processing are the high export costs that are a barrier to accessing the international market and the lack of support from the local government for the coir waste processing business. This study describes the processing of coir waste into products that have economic value using qualitative research methods. The data collection techniques used were observation, interview, and documentation.